ANALYSIS OF THE EFFECT OF RAW MATERIAL PLANNING, INVENTORY CONTROL, AND RAW MATERIAL QUALITY ON THE PRODUCTION PROCESS - Wulandari, Aprilia Nadila; Fatimah, Feti; izzudin, Ahmad (Univesitas Muhammadiyah Tangerang, 2025)
This study analyzes the influence of raw material planning, raw material control, and raw material quality on the production process at the Tofu Home Industry in Kaliwates District, Jember Regency. This study used a sample of 106 Tofu Home Industry employees in Kaliwates District, Jember Regency, who were selected using a census technique. The method used was multiple linear regression analysis. The results of the study showed that the three factors had a significant effect on the production process. This study has a novelty by focusing on the Tofu Home Industry and integrating three main variables in the analysis of the production process. The suggestions from this study provide practical direction for employees so that the industry always pays maximum attention to raw material planning, including monitoring its quality and quantity, to ensure that the production process runs smoothly and produces good quality products. Thus, the industry can meet market needs and increase customer satisfaction. Theoretically, this study contributes to the development of production process theory in small industries and opens up opportunities for further research.